Functional analysis of tanshinone IIA that blocks the redox function of human apurinic/apyrimidinic endonuclease 1/redox factor-1 - Sui J; Li M; Qian C; Wang S; Cheng Y; Chen BP; Wang D (Dove Medical Press, 2014)
Jiangdong Sui,1,2 Mengxia Li,1 Chengyuan Qian,1 Shufeng Wang,3 Yi Cheng,1 Benjamin PC Chen,2 Dong Wang1 1Cancer Center, Daping Hospital and Research Institute of Surgery, Third Military Medical University, Chongqing, People’s Republic of China; 2Division of Molecular Radiation Biology, Department of Radiation Oncology, University of Texas Southwestern Medical Center, Dallas, TX, USA; 3Institute of Immunology, PLA, College of Basic Medical Sciences, Third Military Medical University, Chongqing, People’s Republic of China Abstract: Apurinic/apyrimidinic endonuclease 1/redox factor-1 (APE1/Ref-1) is a multifunctional protein possessing both DNA repair and redox regulatory activities. It has been shown that blocking redox function leads to genotoxic, antiangiogenic, cytostatic, and proapoptotic effects in cells. Therefore, the selective inhibitors against APE1’s redox function can be served as potential pharmaceutical candidates in cancer therapeutics. In the present study, we identified the biological specificity of the Chinese herbal compound tanshinone IIA (T2A) in blocking the redox function of APE1. Using dual polarization interferometry, the direct interaction between APE1 and T2A was observed with a KD value at subnanomolar level. In addition, we showed that T2A significantly compromised the growth of human cervical cancer and colon cancer cells. Furthermore, the growth-inhibitory or proapoptotic effect of T2A was diminished in APE1 knockdown or redox-deficient cells, suggesting that the cytostatic effect of T2A might be specifically through inhibiting the redox function of APE1. Finally, T2A pretreatment enhanced the cytotoxicity of ionizing radiation or other chemotherapeutic agents in human cervical cancer and colon cancer cell lines. The data presented herein suggest T2A as a promising bioactive inhibitor of APE1 redox activity. Keywords: tanshinone IIA, APE1, redox activity, multifunctional protein